A chromosome-level genome assembly of an early matured aromatic Japonica rice variety Qigeng10 to accelerate rice breeding for high grain quality in Northeast China - Jiang, Shukun; Zhang, Xijuan; Yang, Xianli; Liu, Chuanzeng; Wang, Lizhi; Ma, Bo; Miao, Yi; Hu, Jifang; Tan, Kefei; Wang, Yuxian; Jiang, Hui; Wang, Junhe (Frontiers in Plant Science, 2023)
Early-matured aromatic japonica rice from the Northeast is the most popular rice commodity in the Chinese market. The Qigeng10 (QG10) was one of the varieties with the largest planting area in this region in recent years. It was an early-matured japonica rice variety with a lot of superior traits such as semi-dwarf, lodging resistance, long grain, aromatic and good quality. Therefore, a high-quality assembly of Qigeng10 genome is critical and useful for japonica research and breeding. In this study, we produced a high-precision QG10 chromosome-level genome by using a combination of Nanopore and Hi-C platforms. Finally, we assembled the QG10 genome into 77 contigs with an N50 length of 11.80 Mb in 27 scaffolds with an N50 length of 30.55 Mb. The assembled genome size was 378.31Mb with 65 contigs and constituted approximately 99.59% of the 12 chromosomes. We identified a total of 1,080,819 SNPs and 682,392 InDels between QG10 and Nipponbare. We also annotated 57,599 genes by the Ab initio method, homology-based technique, and RNA-seq. Based on the assembled genome sequence, we detected the sequence variation in a total of 63 cloned genes involved in grain yield, grain size, disease tolerance, lodging resistance, fragrance, and many other important traits. Finally, we identified five elite alleles (qTGW2Nipponbare, qTGW3Nanyangzhan, GW5IR24, GW6Suyunuo, and qGW8Basmati385) controlling long grain size, four elite alleles (COLD1Nipponbare, bZIP73Nipponbare, CTB4aKunmingxiaobaigu, and CTB2Kunmingxiaobaigu) controlling cold tolerance, three non-functional alleles (DTH7Kitaake, Ghd7Hejiang19, and Hd1Longgeng31) for early heading, two resistant alleles (PiaAkihikari and Pid4Digu) for rice blast, a resistant allele STV11Kasalath for rice stripe virus, an NRT1.1BIR24 allele for higher nitrate absorption activity, an elite allele SCM3Chugoku117 for stronger culms, and the typical aromatic gene badh2-E2 for fragrance in QG10. These results not only help us to better elucidate the genetic mechanisms underlying excellent agronomic traits in QG10 but also have wide-ranging implications for genomics-assisted breeding in early-matured fragrant japonica rice.